2022
DOI: 10.3390/ijerph19021016
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Heating, Ventilation and Air-Conditioning (HVAC) Systems in Buildings—An Overview

Abstract: Increasing demand on heating, ventilation, and air-conditioning (HVAC) systems and their importance, as the respiratory system of buildings, in developing and spreading various microbial contaminations and diseases with their huge global energy consumption share have forced researchers, industries, and policymakers to focus on improving the sustainability of HVAC systems. Understanding and considering various parameters related to the sustainability of new and existing HVAC systems as the respiratory system of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 111 publications
0
34
0
Order By: Relevance
“…Haijing, L. et al [19] simulated seven cities in four thermal climate zones, and the results showed that the influence of shading differed significantly under different scenarios, with the variation range of cooling load proportion being about 45% and that of heat load proportion being about 21%. Asim, N. et al [20] proposed measures to improve the efficiency of HVAC system by analyzing related factors affecting the selection of HVAV system in the early design stage, so as to reduce the operation energy consumption. 4) Comparative studies that focus on the applicability of energy consumption simulation software in the design stage.…”
Section: Introductionmentioning
confidence: 99%
“…Haijing, L. et al [19] simulated seven cities in four thermal climate zones, and the results showed that the influence of shading differed significantly under different scenarios, with the variation range of cooling load proportion being about 45% and that of heat load proportion being about 21%. Asim, N. et al [20] proposed measures to improve the efficiency of HVAC system by analyzing related factors affecting the selection of HVAV system in the early design stage, so as to reduce the operation energy consumption. 4) Comparative studies that focus on the applicability of energy consumption simulation software in the design stage.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the research should be expanded in diverse types of residential buildings with different comfort categories in multiple climate zones [32][33][34][35] to evaluate the operation of mixed-mode ventilation effectively in different climate regions and other aspects of energy/cost savings better. In addition, further study should practice research results using dynamic energy simulations in different cases, as well as analyze the relationship between the operation of mixed-mode ventilation and filtration in an HVAC system affected by the indoor/outdoor environment [36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…6 The transfer of heat is also important in the construction industry and heating, ventilation, and heating, ventilation, and air conditioning (HVAC) systems. 7 The goal of HVAC is thermal comfort, and HVAC systems use heat transfer to attain this goal. Insulation, window design, and other energysaving building techniques are all impacted by heat transfer principles.…”
Section: Introductionmentioning
confidence: 99%